Breeding farmer and consumer preferred sweetpotatoes using accelerated breeding scheme and mother–baby trials - Baafi, E.; Akom, M.; Agyeman, A.; Darko, C.; Carey, E.E. (Walter de Gruyter GmbH, 2020)
Increased sweetpotato utilization has become an important breeding objective recently, with much emphasis on the development of non-sweet sweetpotatoes for income and food security in Ghana. The objective of this study was to evaluate 26 elite non-sweet and less sweet sweetpotato genotypes with regard to their release as commercial varieties using mother–baby trial. The 26 sweetpotato genotypes were tested multilocational on-farm across five ecozones from 2016 to 2017. These genotypes were selected from accelerated breeding scheme carried out from 2010 to 2013. There were no year-by-ecozone-by-genotype and year-by-ecozone interactions. However, ecozone-by-genotype interaction was significant for storage root dry matter, beta-carotene, iron and zinc content. This implies that the relative performance of the genotypes for storage root yield was stable across locations and years. Genotypic differences were found for all the traits and indicated that selection of superior genotypes across ecozone was possible. Storage root yield ranged from 7 t/ha to 39 t/ha, while dry matter content ranged from 34% to 46%. The storage root cooking quality preference was comparable with farmers’ check. Ten superior genotypes were identified for release as commercial varieties based on their staple-preferred taste, higher storage root yield, higher dry matter content, earliness, resistance to the sweetpotato virus, sweetpotato weevil and Alcidodes.